Meningkatkan Gaya Hidup Bugar di Kalangan Remaja melalui Evaluasi Hasil Tes Kebugaran Siswa Indonesia - Jannah, Wardhatul; Sitanggang, Joy Parulian; Kaloko, Jetun Litwan; Astia Nababan, Maria Astuti; Bukit, Dauglas Alfredy; Kemit, Sedrahta Arona (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to evaluate the impact of using fitness tests on improving healthy lifestyles among teenagers in Indonesia. In achieving this goal, this study was conducted by observing the effectiveness of fitness tests as a tool to encourage adolescents to adopt an active and healthy lifestyle. The method used is the application of fitness tests to students in several schools in Indonesia. After that, an evaluation of the results of this fitness test was carried out to measure changes in physical activity and awareness of the importance of a healthy lifestyle among teenagers. The research results show that the use of fitness tests can increase students' awareness of the importance of physical activity and a healthy lifestyle. Apart from that, the test results are also able to provide a clear picture of the student's physical fitness condition, allowing for more targeted monitoring of positive behavioral changes. In conclusion, evaluating fitness test results can be an effective tool in improving a fit lifestyle among Indonesian teenagers.